Classifying Geography Textbook Visuals According to the Concept of Direct, Indirect, and Symbolic Experience of Nature - Markus Hilander (MDPI AG, 2023)
Geography textbooks have many visuals, such as maps, graphs, tables, photographs, and illustrations, which makes geography a highly visual school subject. However, previous studies show that geography students can pay surprisingly little attention to textbook visuals. In this article, it is asked what sorts of visuals are there in geography textbooks if they do not attract students' attention. In order to answer the research question, a visual method to approach textbook visuals is developed. The visual method is motivated by Stephen Kellert's concept of direct, indirect, and symbolic experience of nature. Based on the three types of experience of nature, three categories for geography textbook visuals are established respectively: snapshot visuals (deriving from direct experience), landscape visuals (deriving from indirect experience), and abstract visuals (deriving from symbolic experience). The sample covers eight Finnish geography textbooks for grades 7-9 and for one upper secondary school course. The results show that most of the visuals depict landscapes. In addition, there are many abstract visuals, such as maps and illustrations, depicting geographical processes. Instead, only a few snapshots of people in action and snapshots of geographical hazards were identified. In the article, it is suggested that enhancing the role of snapshot visuals in geography education could increase students' interest towards textbook visuals, as well. This is because snapshot visuals can draw students' attention and enable students to express their own feelings and thoughts.